Quantitative Approach to Condensate from Residential Air Conditioners with Different Capacity as Drinking Water - Kasni Sumeru; Triaji Pangripto Pramudantoro; Afif Miftakh Hafidzudin; Mohamad Firdaus bin Sukri; Cecep Sunardi (Bandung State Polytechnic (Politeknik Negeri Bandung), 2022)
During operation, the evaporator of split-type air conditioner (A/C) produces condensate water due to lower evaporator temperature, as compared to dew point temperature of the indoor air. So far, the condensate is considered unimportant and therefore being wasted. The split-type A/C is widely used in high-rise buildings, hotels, shopping areas, and even residential. The study aims to investigate the potential feasibility of the condensate to be used as for drinking water. Of course, treatment of the condensate is required before it can be used as a drinking water. The experiments were carried out in two cities, namely Bandung and Cirebon. Bandung represents a city with a cool climate, while Cirebon represents a city with a hot climate. The capacities of the A/C utilized in Bandung and Cirebon are 0.5 HP and 1 HP, respectively. The quantities of the condensate from the A/C were collected for 24 for hours. The quality of the condensate was benchmarked with guidelines/standard from PERMENKES NO 492/MENKES/PER/IV/2010. The benchmarking process involved testing and evaluation of 22 significant parameters related to water quality for drinking purpose. By utilizing waste condensate water, it is predicted that it can be a vital alternative of potable water in the future